Design of millimeter wave metamaterial array antennas for MIMO-beamforming systems - Janat, Mohanad (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
In 2020 and beyond the 5th generation mobile communication technology will provide wideband connection, fast mobility support, and shall take mobile communication concept to a whole new level. However, the new generation of mobile telecommunications needs a robust antenna, which has an outstanding performance and can support millimeter wave (mmWave) communications that suffers from high path losses. The new antenna design must meet the upcoming 5G requirements that is going through standardization phase currently. a novel antenna design is more critical to the upcoming 5th generation of mobile communication compared to other challenges due to the mmWave utilization that suffers from high propagation path losses and according to that the antenna configuration must have very high directive gain, but it will lead to suppress the viewing area of the antenna which makes it less sensitive receiver. This hard trade off can be balanced by either the gain, without sacrificing coverage like steered beams antenna arrays, or by diversity gain, taking advantage of multipath signals to multiply link capacity like multiple input multiple output (MIMO) array antennas. Two new antenna designs are proposed in this thesis based on beamforming phased antenna array and MIMO beamforming antenna array followed by a detailed simulation study. Metamaterial (MTM) substrates were used in both design to keep the antenna size to a minimum, making them well adapted to the upcoming 5G environment. The first design is beamforming with beam steering capability where the beam direction can be controlled and directed to the receiver direction. Whereas, the second design is a MIMO beamforming array with very high performance, low complexity and high diversity. The steered beam array can control the main beam lobe direction over the intended range of 50 degrees as it is clearly observed in simulation results by changing the varicap. The angle of main beam lobe is controlled by the varying the varicap capacitance value. The antenna resonates at mmWave frequency of 28 GHz and has a maximum gain of 12 dB and bandwidth of 4.3 GHz at reflection coefficient threshold of -10 dB. Furthermore, an evaluation of MIMO array beamforming performance is presented, where the 2X2 MIMO beamforming array consists of 4 sub-arrays which can transmit and receive via two streams. Each sub-array has a gain at the boresight of 13.4 dB from the main lobe in the radiated beam with sidelobes level at -15.99 dB. For uniform excitation the accepted sidelobe level is -13dB as illustrated by Computer Simulation Technology Micro Wave Studio (CST MWS) simulation. The four sub-arrays are resonating at 28 GHz and isolated, where the reflection coefficient is less than -20 dB when the s-parameters observed at 28 GHz. The best isolation achieved is between subarrays 1 and 4 with a value of -44 dB. The isolation between subarrays 2 and 3 is also high with a value of -45 dB. From the S-parameters observation we could analytically calculate and plot envelop correlation coefficient (ECC). The ECC values at 28 GHz between subarrays 1, 4, and 2, 3 are zeros. Generally the ECC values between the antenna elements are very low.